Supply Chain Risk Management untuk Strategi Pengelolaan Sampah Menggunakan House of Risk - Riana, Riska Iva; Immawan, Taufiq; Herdianzah, Yan (Universitas Muhammadiyah Sorong, 2025)
Currently, the waste section of Manggala District, Makassar City, still encounters many risks that commonly occur in the waste management supply chain from the waste source to the Temporary Disposal Site (TPS) and then to the Final Disposal Site (TPA). This causes the volume of waste to increase every day due to the lack of segregation of waste from waste sources so that waste in the TPS is scattered due to the fact that the trash cans are no longer able to accommodate it and finally the TPA is over capacity without any effective handling to reduce the volume of waste. Therefore it is necessary to handle the risks that occur. This study aims to provide recommendations for sustainable mitigation strategies to reduce the impact of risks on waste management using the Delphi method to identify potential risks. Using the House of Risk (HOR) in the risk analysis and evaluation stages to determine mitigation strategies. Research data collection was carried out by observation, interviews, questionnaires, brainstorming, and focus group discussions (FGD). Based on the research results it is known that there are 18 risk events and 65 identified risk agents. Furthermore, a mitigation strategy for risk agents is carried out using 16 preventive actions that have been designed using HOR phase II, for further research it is hoped that it will be able to develop waste management in other sub-districts in Makassar City.